The Tradition of Keleman Asking for Rain in Peniwen Village, Malang - Devina Margaretha Febrianti; Novi Fitia Maliha (PT Pro Panoramic Solution, 2025)
Indonesia is a country rich in culture and ethnic groups. This has given Indonesia a diverse range of traditional cultures and customs that have been passed down through generations and are still preserved today. The diversity of ethnic groups in Indonesia enhances national unity. Various cultures among these groups help unite their communities, with preserved traditions serving as a means to strengthen social bonds. Culture is reflected in the behavior and activities of a community. One preserved tradition is the Keleman Tradition, which seeks God's blessing for rain to begin the rice planting season. This tradition is still practiced in Peniwen Village, Kromengan District, Malang Regency. The study aims to explore the history, practices, significance, and preservation of the Keleman tradition in this community. This study employs a qualitative approach to explore the Keleman tradition in Peniwen Village, which has evolved into a local custom. Due to no rain in October, the Keleman tradition will be held on October 30 at the village hall. This event involves agricultural counseling from local authorities, and residents are expected to bring food for Encek. The tradition serves as a plea for rain and expresses gratitude for safety and sustenance.